Can Policy Facilitate Partial Retirement? Evidence from Germany - Peter B. Berg; Mary K. Hamman; Matthew Piszczek; Christopher J. Ruhm (Institute for the Study of Labor (IZA), 2015)
In 1996, Germany introduced the Altersteilzeit (ATZ) law, which encouraged longer working lives through partial retirement incentives. Using matched pension system and establishment survey data, we estimate changes in part-time employment and retirement after ATZ. We find the policy induced growth in part-time work for men and extended men's expected duration of employment by 1.8 years. As the policy evolved to include an abrupt retirement option, the worklife gain for men fell to 1.2 years. Among women, part-time employment grew less and employment duration changed little initially but later declined by 0.2 years when abrupt retirement became available.
Keywords: J26; 330; partial retirement; Germany